Development of n-Type Porphyrin Acceptors for Panchromatic Light-Harvesting Fullerene-Free Organic Solar Cells - Lee, Un-Hak; Hadmojo, Wisnu Tantyo; Kim, Junho; Eom, Seung Hun; Yoon, Sung Cheol; Jang, Sung-Yeon; Jung, In Hwan (Frontiers in Chemistry, 2018)
The development of n-type porphyrin acceptors is challenging in organic solar cells. In this work, we synthesized a novel n-type porphyrin acceptor, PZn-TNI, via the introduction of the electron withdrawing naphthalene imide (NI) moiety at the meso position of zinc porphyrin (PZn). PZn-TNI has excellent thermal stability and unique bimodal absorption with a strong Soret band (300–600 nm) and weak Q-band (600–800 nm). The weak long-wavelength absorption of PZn-TNI was completely covered by combining the low bandgap polymer donor, PTB7-Th, which realized the well-balanced panchromatic photon-to-current conversion in the range of 300–800 nm. Notably, the one-step reaction of the NI moiety from a commercially available source leads to the cheap and simple n-type porphyrin synthesis. The substitution of four NIs in PZn ring induced sufficient n-type characteristics with proper HOMO and LUMO energy levels for efficient charge transport with PTB7-Th. Fullerene-free organic solar cells based-on PTB7-Th:PZn-TNI were investigated and showed a promising PCE of 5.07% without any additive treatment. To the best of our knowledge, this is the highest PCE in the porphyrin-based acceptors without utilization of the perylene diimide accepting unit.